Pengaruh Pembelajaran Kooperatif Tipe Student Teams Achievement Divisions (STAD) Dan Think-Pair-Share (T-P-S) Terhadap Prestasi Belajar Ditinjau Dari Sikap Ilmiah - Junanto, Tulus (Jurnal Pendidikan Matematika dan IPA, 2010)
The purposes of the research is to obtain effect the using of STAD cooperative learning method and T-P-S toward student achievement from scientific attitude. The research used experiment method. The result of the data analysis based on 5 % level signification were found that: 1) Fcount = 9,2289 in effect of learning method toward students achievement, Fcount = 8,7450 in effect of scientific attitude toward students achievement, Fcount = 4,5246 in interaction between method and scientific attitude for cognitive aspect data while Ftabel = 3,97, 2) Fcount = 5,4759 in effect of learning method toward students achievement, Fcount = 29,9671 in effect of scientific attitude toward students achievement, Fcount = 5,2476 in interaction between method and scientific attitude for afective aspect data while Ftabel = 3,97. The conclusion of this research are : 1) student achievement that using cooperative learning type STAD is better than T-P-S type both of cognitive and affective aspect, 2) the students who have high science attitude get student achievement better than the students who have low science attitude both of cognitive and affective aspect, 3) learning method STAD and T-P-S have different effect toward student achievement to student groups who have different science attitude.Keywords : Student Team Achievement Divisions (STAD), Think Pair Share (T-P-S), Scientific attitude.